Prevalence of gastrointestinal nematodes in sheep and goats in some parts of north-west India - KUMAR, RAJEEV RANJAN; YADAY, C L; GARG, RAJAT; BANERJEE, P S; VATSYA, STUTI (The Indian Journal of Animal Sciences, 2011)
A total of 9261 sheep and 7262 goat faecal samples were examined from April 2001 to March 2006 from different areas of Western Uttar Pradesh, Haryana, Rajasthan and Delhi. 5432 (58.65%) faecal samples of sheep and 3999 (55.060/0) samples of goats were positive for different gastrointestinal nematodes (GIN). Highest prevalence of GIN in sheep and goats was observed during November (69.64%) closely followed by September (66.14%). Maximum prevalence was recorded during the year 2001-2002 and 2002-2003, respectively. The mean EPG was observed to be higher in sheep (317.34) as compared to goats (286.85). Coproculture study revealed Haemonchus contortus as the predominant GIN in sheep and goats followed by Trichostrongylus colubriformis, Oesophagostolnurn colLunbianum and Strongyloides papillosus, however, Bunostomum trigonocephalu111. was recorded only in sheep. Occasionally Trichuris avis in sheep and goats and Chabertia ovina in sheep was also recorded. Â